Challenging behavior in mucopolysaccharidoses types I-III and day-to-day coping strategies: a cross sectional explorative study - Hoffmann, Frederik; Hoffmann, Susanne; Kunzmann, Kevin; Ries, Markus (Orphanet journal of rare diseases, 2020)
Challenging behavior represents a core symptom in neuropathological mucopolysaccharidoses (MPS) and puts major strain on affected families. Although multimodal approaches including behavioral strategies to treatment could be valuable, there is lack of research to the effectiveness of specific measures. This explorative, cross-sectional study is aimed at the collection of parental experiences regarding effective day-to-day measures against challenging behavior in MPS and focuses on 4 major research questions: First: What is challenging behavior in MPS? Second: Which strategies are helpful in the day-to-day coping with challenging behavior? Third: How strong is parental acceptance of illness and the disorder’s impact on family relationships? Fourth: What are beneficial personal and interfamilial strategies for generally coping with the disorder?
Gesehen am 04.11.2020